The impact of price adjustment costs on price dispersion in E-commerce - René Böheim; Franz Hackl; Michael Hölzl-Leitner (Johannes Kepler University of Linz, Department of Economics, 2019)
We analyze price dispersion using panel data from a large price comparison site. We use past pricing behavior to instrument for potential endogeneity that might result from the selection of firms to certain product markets. We find that greater price adjustment costs result in greater price dispersion. Although the impact of price adjustment costs on price dispersion became weaker over time, the causal effect of price adjustment costs on price dispersion is still present at the end of the period. Our results are robust to many alternative empirical specifications. We also test a range of alternative explanations of price dispersion, such as search cost, service differentiation, obfuscation, vertical restraints, and market structure.
Keywords: D40; L11; 330; price dispersion; price adjustment costs; menu costs; e-commerce